2020
DOI: 10.3390/agronomy10091281
|View full text |Cite
|
Sign up to set email alerts
|

Improving of Cherry Fruit Quality and Bearing Regularity by Chemical Thinning with Fertilizer

Abstract: The study’s objective was to evaluate the influence of thinning on the quality and regularity of yield of ‘Regina’ cherries grown on a dwarf Gisela 5 rootstock. The experiments were conducted in the years 2009–2012 in Western Poland. Trees were thinned using a chemical agent, ammonium thiosulphate (ATS), at doses of 20 g ATS L−1, 30 g ATS L−1 and 40 g ATS L−1, and by hand, and the results of chemical and hand thinning were compared with those obtained for unthinned trees. The course of weather conditions in wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 61 publications
0
16
0
Order By: Relevance
“…Plant extracts and plant-derived protein hydrolysates were previously reported to boost C metabolism and to stimulate the biosynthesis of secondary metabolites such as pigments, phenolic comp, and ascorbic acid [66]. Previous studies on sweet cherries demonstrated that inducing an increase in carbohydrate availability for ripening fruits by fruit flower/fruit thinning can result in an increase in soluble solids and anthocyanin concentration and in darker fruit skins [67,68]. Interestingly, the positive effects of the TPEB on soluble solids content and fruit color were not found in the fruits of the cultivar Regina (Table 2 and Figure 2B).…”
Section: Discussionmentioning
confidence: 99%
“…Plant extracts and plant-derived protein hydrolysates were previously reported to boost C metabolism and to stimulate the biosynthesis of secondary metabolites such as pigments, phenolic comp, and ascorbic acid [66]. Previous studies on sweet cherries demonstrated that inducing an increase in carbohydrate availability for ripening fruits by fruit flower/fruit thinning can result in an increase in soluble solids and anthocyanin concentration and in darker fruit skins [67,68]. Interestingly, the positive effects of the TPEB on soluble solids content and fruit color were not found in the fruits of the cultivar Regina (Table 2 and Figure 2B).…”
Section: Discussionmentioning
confidence: 99%
“…fertilizers (ammonium thiosulfate (ATS), urea), and some sulfur compounds [52][53][54][55] [53]. They cause damage to the stigma and anthers, which prevents pollination [56]. Growth regulators, such as hydrogen cyanamide, interrupt dormancy, stimulate uniform development of flower buds, but also cause flower thinning if applied to flowering plants [57].…”
Section: Chemical Thinningmentioning
confidence: 99%
“…In the United States, research has been conducted on the use of cyanoamide, monocarbamide dihydrosulfate, pelargonic acid, endothalic acid and Tergitol TMN-6 as chemical thinning agents. In Europe, studies are carried out on the use of ammonium thiosulfate (ATS) and plant growth regulator 2-chloroethylphosphonic acid (ethephon), which are commonly applied to apple and pear trees during flowering [56,[58][59][60][61][62]. The main objectives of the widespread use of thinning in the cultivation of apples and pears are to improve fruit quality and to prevent alternating bearing [63,64].…”
Section: Chemical Thinningmentioning
confidence: 99%
See 2 more Smart Citations